2016
DOI: 10.1039/c6nr01061j
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence-dependent ionic currents in ultra-small solid-state nanopores

Abstract: Measurements of ionic currents through nanopores partially blocked by DNA have emerged as a powerful method for characterization of the DNA nucleotide sequence. Although the effect of the nucleotide sequence on the nanopore blockade current has been experimentally demonstrated, prediction and interpretation of such measurements remain a formidable challenge. Using atomic resolution computational approaches, here we show how the sequence, molecular conformation, and pore geometry affect the blockade ionic curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 87 publications
(190 reference statements)
0
27
0
Order By: Relevance
“…Actually, previous experimental studies reported that the ratio of measured conductance of the phi29 connector to a-HL biological nanopore compares well with the ratio of cross-sectional areas, because the conductance of a channel is proportional to its cross-sectional area 7 . Moreover, by using atomic-resolution Brownian dynamics method, previous simulation studies reported that decreasing the cross section of the solid nanopore led to an decreased blocked current 51 . Therefore, nanopores with smaller diameters will result in larger signal amplitudes from dsDNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, previous experimental studies reported that the ratio of measured conductance of the phi29 connector to a-HL biological nanopore compares well with the ratio of cross-sectional areas, because the conductance of a channel is proportional to its cross-sectional area 7 . Moreover, by using atomic-resolution Brownian dynamics method, previous simulation studies reported that decreasing the cross section of the solid nanopore led to an decreased blocked current 51 . Therefore, nanopores with smaller diameters will result in larger signal amplitudes from dsDNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…(2010), where the SNR for sensing microRNAs using SiN x increases with decreasing membrane thickness and decreasing pore diameter. Intuitively, SNR decreases with a because ions flowing far from the DNA/RNA in the pore adds noise but do not contribute to the signal (Comer and Aksimentiev, 2016). Similarly, both signal Δ I ~ 1 /h p and noise Irms~1/hp decrease with height but the signal decreases faster and so the SNR decreases with height.…”
Section: Continuum Ion Transportmentioning
confidence: 99%
“…Besides a high SNR for individual blockade events, it is desirable for distinguishing bases to have a high sensitivity (Comer and Aksimentiev, 2016; Garaj et al ., 2013) S=ΔIaDNA=VR2ΔRaDNA2γaDNAVhpπa4R2, where we used Δ R from Eq. 7, and assumed a=a2aDNA2 to be small, clearly necessary for large sensitivity.…”
Section: Continuum Ion Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Combinations of experiments and simulations have revealed a wealth of knowledge on DNA translocation through nanopores [ 41 ]. Molecular dynamics simulations have been used to understand the role of nucleotide orientation and neighboring nucleotide chemistry on the passage of ions through the nanopore [ 42 , 43 ]. Drnjic and coworkers have shown that hm 5 C modification in a double stranded DNA can be distinguished from its canonical counterpart using a solid-state nanopore [ 44 ].…”
Section: Introductionmentioning
confidence: 99%